The Association between Asphyxia and Interleukin (IL)-6 and IL-1β Levels in Neonates - Nenden Nursyamsi Agustina; Muhammad Sholeh Kosim (Journal of Biomedicine and Translational Research, 2021)
Background: Neonatal asphyxia is a respiratory failure during and just after birth. It can cause morbidity and mortality in neonates.Interleukin (IL)-6 and IL-1β are inflammatory cytokines produced by neuronal cells in early response to brain injury due to asphyxia. However, their role in neonatal asphyxiais remain elusive.Objective: To determine theassociation between asphyxia and serumIL-6 and IL-1β levelsin neonates.Methods: Across-sectional study was conducted on neonates diagnosed with moderate to severe asphyxia who hospitalized atthe Dr. Kariadi General Hospital Semarang Indonesia from December 2013 to May 2014. The subjects were examined for serum IL-6 and IL-1β. Blood samples were obtained from umbilical vein in the first 24 hours of life. Serum IL-6 and IL-1β levelswere measured using immunoassay. Dependent variable were IL-6 and IL-1β level. Bivariate analysis was performed using chi-square test, for the assessment of the association between dependent and independent variables. A p-value of less than 0.05 was considered statistically significant.Result: A total of 54 subjectswere enrolled in this study. No significant difference between moderate and severe asphyxia neonatesin term ofsex, birthweight,type of delivery, neonate’s mother age, gestational age, and parity. Levels of IL-6 and IL-1β levels wereincreased significantly in both moderate and severe asphyxiagroups, and the levels were significant higher in the severe asphyxia than that of in the moderate, p=0.003 and p=0.007, respectively.Conclusion:There was association between asphyxia and IL-6 and IL-1β levelsin neonates.IL-6 and IL-1β levelswere increased in neonates with moderate and severe asphyxia, with extend of increase was significant higherin the later.